Travelling back in time. - Newman, Kim (Sight & Sound, 2004)
This article describes the Britishing Broadcasting Company's DVD release of episodes of "Doctor Who". The BBC will release episodes, judged to be representative-to-outstanding, from each of the television program's eight incarnations. Most episodes are shown as they appeared on television, and the DVD's include many extras, including cross-promotional material.